PODCAST COMO HERRAMIENTA DE COMUNICACIÓN PARA PERIODISTAS DEPORTIVOS DEL CIRCULO DE PERIODISTAS DE LOS RIOS, AÑO 2022 - Echeverria Mera, Juan Fernando (2022)
The objective of this research work is to determine the incidence of the podcast as a communication tool for sports journalists from the Sports Journalists Circle of Los Ríos, in the year 2022. For which, the importance of the podcast as a communication tool was analyzed, the main technological and public access advantages of this system were identified, for which a bibliographic study of the implementation of this tool in other contexts was carried out, and a field study to measure the knowledge of the subject by journalists in the province of Los Ríos and their willingness to implement the podcast in their journalistic work. Finally, a training plan on the use of the podcast as a communication tool was proposed for the members of the Sports Journalists Circle of Los Ríos.